Determinants of CSRD in NonAsian and Asian Countries: a Literature Review - Abbas Almtoor, Yasir Abdullah; Ahmad Zaluki, Nurwati Ashikkin; Abd Rahim, Nazahah (Emerald Publishing, 2021)
Purpose – The purpose of this paper is to review the current status of research works on corporate social responsibility disclosure (CSRD) in both non-Asian and Asian countries. It seeks to provide an overview of existing literatures to facilitate future research. Design/methodology/approach – The present study used the content analysis of 64 empirical research papers from 41 countries from 1990 to 2020 to show the rapid development of and global focus on CSRD. Various CSRD measures had been used in previous researches on the extent and quality of disclosure. Findings – Company characteristics, namely, company size, age, profitability, industry, share price performance and corporate governance mechanisms and their impact on CSRD, were investigated. Crucial variances between the determinants of CSRD in non-Asian and Asian countries were also reviewed. In non-Asian countries, especially the advanced ones, specific stakeholders such as regulators, the environment, shareholders, ownership and media are considered very significant in the disclosure of CSR information. Meanwhile, in Asian countries, CSRD is more affected by external strength and stakeholders, which include international capital markets, creditors, the environment, international media and ownership. Research limitations/implications – The determinants of CSRD, namely, community, workplace, environment and marketplace issues received very little pressure from the public. This paper suggests that there is a need for more studies examining CSRD in non-Asian and Asian (emerging) countries. Social implications – Business organisations in non-Asian and Asian countries should take social practices into consideration in their CSRD decision-making. This review highlights the significance of merging organisational and social activities. Originality/value – This study adds value by examining CSRD aspects that were not reviewed in previous studies on CSRD in non-Asian and Asian countries. This study provides a comprehensive review of the determinants of CSRD in both non-Asian and Asian countries